Implementasi Sistem Bagi Hasil Pertanian Di Kecamatan Bontotiro - Marshanda Sultan; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to explore the sharecropping system in Bontotiro District, Bulukumba Regency, South Sulawesi, with a particular focus on the underlying social and cultural values. Employing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation, with participants selected using purposive sampling. The findings reveal that the sharecropping system is conducted informally, relying heavily on trust, kinship, and the principle of distributive justice. This practice functions not only as an economic mechanism but also reflects communal values such as mutual cooperation, social flexibility, and strong community bonds. The discussion highlights that this system is a form of local wisdom that persists despite the absence of formal agreements. However, modernization and social changes call for innovations such as simple documentation and the strengthening of local institutions to ensure the system’s sustainability and fairness in the future.